LAYANAN INTERNET SPEEDY PT TELKOM MUARA JAWA DAN KEPUASAN KONSUMEN - Elfreda Aplonia Lau, Mardiah Apriliani Tanjung Sari, LCA. Robin Jonathan, (EKONOMIA, 2015)
This study aims to determine the level of customer satisfaction based Internet service Speedy and where the dominant variable effect between service quality and service orientation towards customer satisfaction PT. Telkom Muara Jawa. Problem formulation in this research are as follows: a) Is Speedy internet service PT.Telkom Muara Jawa which includes quality of service and service orientation affects customer satisfaction? b) where the dominant variable between quality to satisfaction at the speedy internet service PT.Telkom Muara Jawa.Population in this research is that consumers spedy PT.Telkom Muara Jawa totaling 170 pelanggan.Sampel used in this study were 99 customers who use the internet service speedy PT Telkom Branch Muara Jawa. Sample determination Solvin formula used by Umar (2008: 127) with the formula n = N / 1 + N. e2. Basic theory Marketing Management include: Understanding Marketing, Understanding Services, Marketing Services, Quality of Service, Service Orientation, Customer Satisfaction and Factors Determining the Level of Satisfaction. The analysis tool uses multiple regression analysis is regression equation that measures the relationship between the variables of service quality and service orientation towards customer satisfaction.Based on the analysis of statistical data, indicators in this study are valid and variables are realibel. In the classic assumption test, regression model to meet the assumptions of normality, free multicoloniarity, no autocorrelation and did not happen heteroskedastisitas.Hasil regression equation can be explained that the constant coefficient (a) is positive at 6.475, meaning that if the value of X1 and X2 is equal to zero, then consumer satisfaction is equal to 6.475. The independent variables namely the quality of service and service orientation positive effect on customer satisfaction, meaning that if the independent variables rise, then the dependent variable also increased, and if the independent variables down, then the dependent variable was also down. Of the two variables that affect customer satisfaction on PT Telkom Speedy Internet service branch Muara Jawa, the most dominant variable is a variable orientation based on the results of the t test. Service orientation variable has a value of t count most large compared with the variable quality of service with a significant level of the smallest.Â Thus Hypothesis which states that the service orientation of the dominant variable effect on customer satisfaction proven and accepted.